The Impact of Financial Literacy, Invesment Decision-Making, Risk Tolerance, and Behavioral Biases on Individual Invesment Performance - Rahmiyati, Nekky; Somodiharjo, Kadari (Eastasouth Institute, 2025)
This study investigates the influence of financial literacy, investment decision making, risk tolerance, and behavioral biases on individual investment performance among investors in Indonesia. Using a quantitative approach, data were collected from 200 respondents through a structured questionnaire using a 5-point Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that all four variables—financial literacy, investment decision making, risk tolerance, and behavioral biases—have a significant and positive effect on individual investment performance. Financial literacy and investment decision making emerged as the most dominant predictors, while risk tolerance and behavioral biases also contributed positively. These findings highlight the importance of enhancing financial knowledge, promoting structured decision-making, and managing psychological influences to improve investment outcomes. The study contributes to both the behavioral finance literature and practical financial education strategies in the Indonesian context.